Enhancing work-life balance through physical and recreational activities - Andreia TĂRCĂIET; Raluca BUHAȘ (GeoSport for Society)
The interplay between professional and personal life significantly impacts individual well-being, making work-life balance an essential topic of study. This research investigates how individuals maintain equilibrium between these domains, with a focus on physical and recreational activities as balancing strategies. Using a qualitative exploratory design, semi-structured interviews with 12 respondents in Bihor, Romania, revealed diverse attitudes, behaviors, and strategies for achieving work-life balance. Participants highlighted the pivotal role of physical activity, mindfulness, and clear boundaries between work and family life. Barriers to balance included limited time, stress, and professional demands, which adversely affect physical and mental health, interpersonal relationships, and job performance. Respondents reported using strategies such as outdoor activities, exercise, and mindfulness to mitigate stress, enhance energy, and foster well-being. The findings underscore the necessity of individual and organizational initiatives to support work-life balance, suggesting that physical and recreational activities are not only stress alleviators but also boosters of productivity and quality of life. Future research should expand on the sample size and explore organizational interventions to enrich our understanding of effective work-life balance strategies.